REDD1 (regulated in development and DNA damage-1)/autophagy inhibition ameliorates fine particulate matter (PM2.5) -induced inflammation and apoptosis in BEAS-2B cells. Issue 1 (1st January 2021) - Li, Yan; Xu, Xiaoxiao; Wang, Liyan; Li, Xuemei; Liu, Running; Zhang, Li; Xu, Yali
ABSTRACT: This study aimed to investigate the implication of REDD1 on airborne particle matter-induced lung injury and whether it is mediated through autophagy. Cell viability in BEAS-2B cells induced by PM2.5 was measured by CCK-8. RT-qPCR and Western blot were performed to determine mRNA and protein levels of REDD1 as well as inflammatory cytokines, respectively. Cell apoptosis was observed with TUNEL staining. The expression of autophagy-related genes was detected by Western blot. Autophagy level was observed with GFP-LC3 staining. PM2.5 induced the expression of REDD1 in BEAS-2B cells. The inhibition by silencing REDD1 ameliorated the viability damage, blocked the inflammatory response and reduced the number of apoptotic BEAS-2B cells all induced by PM2.5. It was also found that PM2.5 induced autophagy in BEAS-2B cells, which was reversed by interference with REDD1. Furthermore, interference with REDD1 alleviated PM2.5-induced cell damage, inflammatory response and apoptosis in BEAS-2B cells through inhibiting autophagy. REDD1/autophagy inhibition ameliorates PM2.5-induced viability damage, inflammation and apoptosis in BEAS-2B cells. Graphical Abstract: uf0001